Experimental and numerical study on the orthogonal and oblique impact on water filled pipes - Hussain Shah, Qasim (Pergamon, 2011)
A 300 mm long piece of copper (ASTM B280) pipe with an outer diameter of 35 mm and 0.7 mm wall thickness was subjected to a rigid steel pipe impact under a drop weight loading configuration where the pipe was simply supported at its ends. Differences in deformation features for a pipe filled with water and an empty pipe were investigated for two configurations namely orthogonal and oblique impact. Compared to orthogonal pipe impact the oblique pipe impact has not been reported in the literature. It is hoped that current work would serve as a first step in this direction. Finite Element Method coupled with Smooth Particle Hydrodynamics (SPH) available in LS-DYNA was used to simulate the empty and water filled pipe impacts under orthogonal and oblique configurations respectively. Fluid structure interaction (FSI) during the water filled pipe impact was successfully modeled using SPH which is a simple method for predicting the short duration FSI events. Experimental results of the effect of varying D/T ratio on the empty and water filled pipes have been reported.